O direito fundamental à boa administração : a tutela da probidade administrativa como instrumento de efetivação de direitos fundamentais - Neves, Rodrigo Santos (2023)
he research analyzed the essential role of the State in the realization of fundamental rights, with the need for a Public Administration linked to the constitutionally signed commitments, of a democratic State of Law. It examined the fundamental right to good administration, enshrined in the Charter of Fundamental Rights of the European Union, as a potential model for promoting an efficient Public Administration. Based on the deductive method, a bibliographical research was carried out and sought to present the fundamental right to good administration, based on its discussion in European Community Law. It investigated the forms of protection of fundamental rights, as parameters of state activity and analyzed how the protection of administrative probity can contribute to the realization of the fundamental right to good public administration, in Brazilian law, based on the theory of fundamental goods. In addition, it proposed that administrative improbity in Brazil should be used to combat only dishonest acts by public agents, to avoid excessive control practices that could discourage innovation in Public Administration. Based on the theory of fundamental assets, by Luigi Ferrajoli, the thesis expanded the concept of public property and concluded that not all cases of maladministration constitute an act of administrative impropriety, but only in cases of willful conduct and when there is damage to the public property. Finally, the need for a more proactive action by the Public Administration was highlighted, which includes intensified planning and risk assessment to ensure the realization of fundamental rights.